For Slow Research. (12th September 2015) - Kuus, Merje
Abstract: This essay addresses a relatively neglected practical aspect of critical policy studies: the pressure to produce many research outputs. That pressure emanates in part from the fast‐paced policy world studied by the researcher, and in part (perhaps even more significantly) from the university environment of the researcher herself. The essay highlights how the tendency towards output‐driven or fast research operates and what analytical traps it engenders. My goal is to spell out, more explicitly than is commonly done, why the push toward fast research is problematic on analytical grounds and why it ought to be resisted on these same grounds. I call for slow research to underscore that context‐sensitive critical investigation of a social field, such as policy, is a necessarily slow process.